Mother's education about under-five nutrition as prevention of stunting and malnutrition - Lusia Henny Mariati; Yohana Jehani (Universitas Muhammadiyah Magelang, 2022)
Malnutrition that occurs in the first thousand days of life will have an impact on children's lives in the future. The results of previous studies that were carried out were known that from 107 under-five-children, there were 32 under-five-children with under nutritional status in Bangka Kenda Village. This activity aims to improve a mother's knowledge about the importance of fulfilling toddler nutrition starting from infancy by giving exclusive breastfeeding for six months, then continuing with additional food. As well as knowledge about nutrition needed by under-five-children. The activity begins with a pre-test, then continues with counseling activities, and at the end, a post-test evaluation of the mother's understanding of the counseling material. The participants were 35 people. The results of the activity showed an increase in the mother's knowledge before and after counseling.